2016
DOI: 10.1186/s12906-016-1218-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of fermented Cyclopia intermedia against UVB-induced damage in HaCaT human keratinocytes

Abstract: BackgroundThe fermented leaves and stems of Cyclopia intermedia are used to brew honeybush tea, a herbal tea indigenous to South Africa. The aim of this study was to evaluate the protective effect of fermented honeybush extracts (FH ex) and scale-up fermented honeybush extracts (SFH ex) against ultraviolet B (UVB)-induced damage in HaCaT keratinocytes. To this end, we examined UVB-induced cell viability, antioxidant enzymes, and inflammatory mediators in HaCaT cells.MethodsUVB significantly decreased HaCaT cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…In this regard, mangiferin has been shown to possess cytoprotective and anti-genotoxic activity in vitro [70]. A recent study also reported on the antioxidant and anti-inflammatory potential of fermented C. intermedia extract in a pre-treatment UVB-HaCaT model further supporting the proposed photo protective properties of honeybush in the skin [71]. Future studies on rooibos and species-specific honeybush aqueous extracts should investigate the role of iron-related pro-oxidant mechanisms in effecting mitochondrial dysfunction, enhancement of oxidative stress and apoptosis as well as the subsequent removal of UVB damaged keratinocytes and the attenuation of inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…In this regard, mangiferin has been shown to possess cytoprotective and anti-genotoxic activity in vitro [70]. A recent study also reported on the antioxidant and anti-inflammatory potential of fermented C. intermedia extract in a pre-treatment UVB-HaCaT model further supporting the proposed photo protective properties of honeybush in the skin [71]. Future studies on rooibos and species-specific honeybush aqueous extracts should investigate the role of iron-related pro-oxidant mechanisms in effecting mitochondrial dysfunction, enhancement of oxidative stress and apoptosis as well as the subsequent removal of UVB damaged keratinocytes and the attenuation of inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…. HU-018 was prepared as per a previously described method [7] with slight modifications. In brief, honeybush (Cyclopia intermedia) was obtained from Rooibos Ltd. (Clanwilliam, South Africa).…”
Section: Preparation Of Hu-018mentioning
confidence: 99%
“…e detailed methods have been described previously [7]. In brief, HaCaT cells were purchased from CLS Cell line service (Eppelheim, Germany) and maintained in Huons Co., Ltd. (Gyeonggi-do, Korea).…”
Section: Cell Culture and Uvb Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…[91]. The anti-inflammatory effects of rooibos and honeybush may involve a reduction in inflammatory cytokines such as IL-6, TNF-α, COX2 [91,92,94]. It may also involve a reduction in neutrophil adhesion, and other mechanisms [96], Table 1.…”
Section: [101]mentioning
confidence: 99%